2020
DOI: 10.1101/2020.02.24.963215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ANME-1 archaea drive methane accumulation and removal in estuarine sediments

Abstract: Uncultured members of the Methanomicrobia called ANME-1 perform the anaerobic oxidation of methane (AOM) through a process that uses much of the methanogenic pathway. It is unknown whether ANME-1 obligately perform AOM, or whether some of them can perform methanogenesis when methanogenesis is exergonic. Most marine sediments lack advective transport of methane, so AOM occurs in the sulfate methane transition zone (SMTZ) where sulfate-reducing bacteria consume hydrogen produced by fermenters, making hydrogenotr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…More surprisingly, contrary to the paradigm that gaseous alkane-oxidizing archaea normally occur where alkanes and sulfate coexist, we observed that ANME-1, ethane-oxidizing and butane-oxidizing archaea were also actively present in sulfate-depleted sediments. Based on their occurrence and activity in shallow coastal sediment cores from Aarhus Bay and White Oak River Estuary, ANME-1 has been proposed to be capable of reverse methanogenesis in sulfate-methane transition or sulfate-depleted sediments [55][56][57] . It is also possible that members of ANME-1 are contributing to methane production in the deep sea cold seep sediments investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…More surprisingly, contrary to the paradigm that gaseous alkane-oxidizing archaea normally occur where alkanes and sulfate coexist, we observed that ANME-1, ethane-oxidizing and butane-oxidizing archaea were also actively present in sulfate-depleted sediments. Based on their occurrence and activity in shallow coastal sediment cores from Aarhus Bay and White Oak River Estuary, ANME-1 has been proposed to be capable of reverse methanogenesis in sulfate-methane transition or sulfate-depleted sediments [55][56][57] . It is also possible that members of ANME-1 are contributing to methane production in the deep sea cold seep sediments investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…This lineage is closely related to ANMEs recovered from cold, anoxic habitats, such as seafloor seep sediments, methane hydrates, and hypersaline anoxic basins, and distinct from previously described ANME-1 phylotypes from Sonora Margin cold seep sediments and potentially thermophilic ANME-1 phylotypes from Guaymas Basin hydrothermal sediments ( Biddle et al., 2012 ; Holler et al., 2011 ). Although ANME-1 archaea were generally assumed to be obligate methanotrophs, this assumption has been challenged and this lineage has been proposed as potentially methanogenic, based on its occurrence and activity in sulfate-depleted sediments ( Lloyd et al., 2011 ; Kevorkian et al., 2020 ); thus, the biogeochemical role of these archaea would be modulated by the presence or absence of sulfate or concomitant changes in electron donors. ANME-2 and cultured methanogenic lineages were observed in low percent abundances in all cores in this study ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Desulfatiglans sp. have been found to cooccur with ANME-1 and SEEP-SRB in estuarine sediments [ 65 ]. It is, however, unknown whether the sulfur compound reduction by Desulfatiglans sp.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ANME-1b has been shown to also be capable of methanogenesis, specifically under high H 2 concentrations [ 65 ]. Although the concentration of H 2 in the incubations was not measured, H 2 may have built up as the consumption of H 2 by SRB was likely inhibited by molybdate.…”
Section: Discussionmentioning
confidence: 99%